OPTIMALISASI PERAN PPNS BEA DAN CUKAI DALAM PENANGANAN PERKARA KEPABEANAN PERDAGANGAN SATWA DILINDUNGI - Zakariya, Rizki (Politeknik Keuangan Negara STAN, 2020)
ABSTRACT: The rise of illegal wildlife trade threatens Indonesia's biodiversity. This was compounded by the development of an increasingly organized and transnational mode of perpetrators of crime. Therefore, it is necessary to carry out optimal and up-to-date law enforcement efforts for illegal wildlife traffickers, particularly by the Civil Servant Investigator at the Directorate General of Customs and Excise. The results of this study indicate the urgency of optimizing the role of customs and excise PPNS in handling customs cases of trade in protected animals because of the increase in protected wild animals that are threatened with extinction; weak strength of evidence of illegal wildlife trade cases at the trial; and the development of an illegal wildlife trade crime mode. Then the optimization efforts can be made by pursuing assets of perpetrators of crime, the use of electronic evidence, and strengthening the cooperation of national and multi-national institutions. So hopefully with these efforts, the purpose of this writing, namely the handling of protected wildlife trade cases run optimally by PPNS Directorate General of Customs and Excise. This research is a qualitative normative juridical research study using a statute approach, a case approach, and a comparative approach.Keywords: Biodiversity, Trade, Animals, Protected. ABSTRAK: Maraknya perdagangan satwa liar ilegal mengancam keanekaragaman hayati Indonesia. Hal itu ditambah dengan berkembangnya modus pelaku kejahatan yang semakin terorganisir dan transnasional. Oleh karena itu, perlu dilakukan upaya penegakan hukum secara optimal dan mutakhir kepada para pelaku perdagangan satwa liar illegal, khususnya oleh Penyidik Pegawai Negeri Sipil Direktorat Jenderal Bea dan Cukai. Hasil penelitian ini menunjukan urgensi optimalisasi peran PPNS Bea dan Cukai dalam penanganan perkara kepabeanan perdagangan satwa dilindungi karena meningkatnya satwa liar dilindungi yang terancam punah; lemahnya kekuatan pembuktian perkara perdagangan satwa liar illegal di persidangan; dan berkembangnya modus kejahatan perdagangan satwa liar ilegal. Kemudian upaya optimalisasi tersebut dapat dilakukan dengan pengejaran aset pelaku kejahatan, pemanfaatan bukti elektronik, dan penguatan kerjasama lembaga nasional maupun multi nasioanl. Sehingga diharapkan dengan upaya tersebut, maka tujuan penulisan ini, yakni penanganan perkara perdagangan satwa liar dilindungi berjalan optimal oleh PPNS Bea dan Cukai. Penelitian ini merupakan penelitian hukum yuridis normatif kualitatif dengan menggunakan pendekatan undang-undang (statute approach), pendekatan kasus (case approach), dan pendekatan komparatif (comparative approach).Kata Kunci: Keanekaragaman Hayati, Perdagangan, Satwa, Dilindungi.